Предмет: Алгебра, автор: Logetx

упростите выражение:
а) (2x+1)(2x-1)
б) (3-y²)(y²+3)
в) (4a²+5)²-25
г) (n-1)(n²+n+1)

Ответы

Автор ответа: ulyanovaa7
0

Объяснение:

а) 4х²-2х+2х-1 = 4х²-1

б) 3у²+9-у⁴-3у² = 9-у⁴

в) 16а⁴+40а²+25-25 = 16а⁴+40а²

Автор ответа: ПетяСемечкин
1
  1. Квадрат разности: (2x+1)(2x-1)=4x^{2}-1.
  2. Квадрат разности: (3-y^{2})(y^{2}+3)=(3-y^{2})(3+y^{2})=9-y^{4}.
  3. Квадрат суммы первого члена выражения, далее лишь сокращение: (4a^{2}+5)^{2}-25=\\=16a^{4}+40a^{2}+25-25=\\=16a^{4}+40a^{2}=\\=8a^{2}(2a^{2}+5).
  4. Разность кубов: (n-1)(n^{2}+n+1)=n^{3}-1.
Похожие вопросы